Pengaruh Pembelajaran IPS Berbasis Kearifan Lokal Terhadap Rasa Cinta Tanah Air Siswa Di SD Negeri 040457 Berastagi - Ginting, Nurlia; Handini, Frida Dian; Nadya Safira Br; Ginting , Sarmina Mutiara Sari Br (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the effect of local wisdom-based Social Studies (IPS) learning on increasing students love for their homeland at SD Negeri 040457 Berastagi. This study uses a quantitative approach with a pre experimental design of one group pretest posttest. The research subjects consisted of 24 fifthgrade students. The data collection instrument was a test designed to measure the level of love for their homeland before and after the treatment of local wisdom-based IPS learning. The results showed that local wisdom-based IPS learning had a significant effect on increasing students love for their homeland at SD Negeri 040457 Berastagi.